Implementasi Metode K-Means Clustering untuk Mengklasterikasikan Perangkat Elektronik dengan Teknik Pengolahan Citra - Ryan Firmansyah; Agung Ramadhanu (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2026)
Grouping electronic devices such as computers, laptops, and smartphones will be very useful in situations where there are a large number of devices to manage, for example in companies, schools, or service centers. This study uses the k-means clustering method with image processing techniques through the Matlab application. The test data used was taken from the internet, consisting of 30 samples comprising 10 computers, 10 laptops, and 10 smartphones. In accordance with the existing dataset, clustering will be performed on three types of electronic devices, namely computers, laptops, and smartphones. After conducting various tests and model designs, the overall accuracy of the model is 100%. This research can cluster 30 samples consisting of 10 computer images, 10 laptop images, and 10 smartphone images. All samples used were taken from the internet.